EFISIENSI PEMANFAATAN LAHAN PADA SISTEM TUMPANGSARI DENGAN BERBAGAI JARAK TANAM JAGUNG DAN VARIETAS KACANG HIJAU - Desi Lestari; Edhi Turmudi; Dotti Suryati (Program Studi Ilmu Tanah Fakultas Pertanian UNIB, 2019)
[EFFICIENCY OF LAND USE IN MULTIPLE CROPPING SYSTEM WITH VARIOUS CORN PLANT AND MUNG BEAN VARIETIES]. This study aims to find out the precise planting distance of corn with mung bean varieties that are suitable for increasing the efficiency of land use in terms of ecology and agronomy. Research has been carried out in the agricultural land in September 2018-January 2019 using a split-plot design. The main plot of planting spacing of corn which is 60 cm x 30 cm, 90 cm x 30 cm, and 120 cm x 30 cm, subplots ie mung bean varieties (Kutilang, Vima-1, Vima-2, Vima-3). As a comparison of intercropping systems, monocultures are cultivated by corn and mung beans. The results showed that in general intercropping of maize and mung bean NKL> 1, ecologically and agronomically efficient. However, this efficient level can be distinguished based on the spacing of corn and mung bean varieties. The best ecological efficiency at 120 cm x 30 cm corn spacing, while the best agronomic efficiency in Virna-3 mung bean varieties.